Performing intimacy: slavery and the woman's voice in eighteenth-century Marathi lavani. Issue 2 (3rd July 2021) - Kulkarni, Kedar A.
ABSTRACT: This article provides an optic for understanding the genre of the Marathi love lyric, lavani (lāvaṇī), and its emotionality. The genre reached its greatest popularity during the turn of the nineteenth century, receiving broad popular support as well as patronage from the Maratha State. Often contrasted with the povada (povāḍā), defined essentially as a heroic ballad that recounts the feats of larger than life historical persons, the two have been seen in tandem, paired for their characterization of masculine valour and feminine eros. Each genre, relying on the other to form a complete picture, providing the appropriate context in a dialogue of genres. Despite the contrast and obvious references to warfare in the povada, however, most scholars have not acknowledged the eros of lavani as a product of its historical circumstances. Instead, generations of scholars have often characterized lavani as immoral, about women who are ready to swindle heroic men out of their hard-earned riches – riches earned from plunder and warfare in the eighteenth century. In this article, I steer away from moralizing discourses, and instead historicize the lavani's aesthetics and emotionality within the contexts of warfare, displacement, and slavery – the material conditions under which lavani reached its apex. I consider the emotional language of the lavani as a desire for social intimacy, attachment, and protection, rather than an attempt at duplicity. The Maratha State frequently sold slaves for revenue generation, and often even granted slaves in lieu of payment; these activities disproportionately affected women. In reading the lavani genre, especially the woman's voice, within its historical contexts, therefore, I argue for a materialist understanding of the lavani's emotionality.